2015
DOI: 10.1177/0194599815587908
|View full text |Cite
|
Sign up to set email alerts
|

Increased Resident Research over an 18‐Year Period

Abstract: There has been a significant increase in resident publications over time, coinciding with the implementation of work hour restrictions. T32 grants were most predictive of increased resident publications, while PhD degrees were not significantly associated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…10 Although residents with T32 grants have been found to produce more publications in residency than those without, residents with PhDs did not produce more publications than their colleagues without the extra training. 10 There has yet to be any study demonstrating whether or not such formalized research training leads to academic success later in an otolaryngology resident's career.…”
Section: Introductionmentioning
confidence: 97%
“…10 Although residents with T32 grants have been found to produce more publications in residency than those without, residents with PhDs did not produce more publications than their colleagues without the extra training. 10 There has yet to be any study demonstrating whether or not such formalized research training leads to academic success later in an otolaryngology resident's career.…”
Section: Introductionmentioning
confidence: 97%
“…A recent study by Chen and colleagues showed a significant increase in the number of resident publications in the last few years [8]. While it is generally felt that publishing as a medical student and/or resident helps demonstrate proficiency in the CanMEDS “Scholar” role [9], a study involving general internal medicine residents [10] revealed that having pre-residency publications was not associated with higher evaluations in the scholar category.…”
Section: Introductionmentioning
confidence: 99%
“…Six studies examined prior publication record related to past research experience [ 12 , 13 , 22 , 31 , 34 , 35 ], of which three found this to be associated with increased productivity [ 12 , 34 , 35 ]. One study also observed that domestic medical graduates were more likely to publish than those who attended foreign medical schools [ 12 ].…”
Section: Resultsmentioning
confidence: 99%